2009
DOI: 10.1007/s12011-009-8441-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Serum Manganese, Zinc, Calcium, Copper and Magnesium Level in Panic Disorder Patients

Abstract: The purpose of the study was to determine the serum concentration of trace elements of panic disorder patients and to find out the relationship between trace element levels and nutritional status or socio-economic factors. The study was conducted among 54 panic disorder patients and 52 healthy volunteers. Patients were recruited from Bangabandhu Sheikh Mujib Medical University by random sampling. Serum trace element concentrations were determined by flame atomic absorption spectroscopy (for Mg, Zn, Ca, and Cu)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Another study showed the copper concentration of lung as 1.91±1.30 mg/L and serum copper concentration as 0.85±0.19 mg/L [10]. Another study in panic disorder patients, serum copper level was found at 0.8 3±0.23 mg/L [11]. In our study, the serum copper level of workers was found statistically higher than the control group.…”
Section: Discussionsupporting
confidence: 48%
“…Another study showed the copper concentration of lung as 1.91±1.30 mg/L and serum copper concentration as 0.85±0.19 mg/L [10]. Another study in panic disorder patients, serum copper level was found at 0.8 3±0.23 mg/L [11]. In our study, the serum copper level of workers was found statistically higher than the control group.…”
Section: Discussionsupporting
confidence: 48%
“…Various studies report blood concentrations of manganese between 0.15 and 7 M (7,8,26,27). Some studies have reported lower Mn 2ϩ levels in lymphocytes (7), plasma, and hair samples (8) of type 2 diabetic patients and in the heart and aorta tissue of patients with atherosclerosis when compared with those of healthy controls (9).…”
Section: Discussionmentioning
confidence: 99%
“…In the peripheral and central nervous systems they play important functional roles and are also components in nervous tissue (3)(4)(5)(6)(7)(8). Imbalances in the optimum levels of these elements may adversely affect biological processes and are associated with many psychiatric diseases including schizophrenia (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%